2007
DOI: 10.1007/s10562-007-9023-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative dehydrogenation of n-butane over mesoporous VO x /SBA-15 catalysts

Abstract: Mesoporous VO x /SBA-15 catalysts with different V contents were evaluated for the oxidative dehydrogenation of n-butane and characterized by N 2 adsorption, XRD, HRTEM, H 2 -TPR, NH 3 -TPD, XPS, and EPR techniques. Compared to conventional V 2 O 5 /SiO 2 catalysts, the VO x /SBA-15 catalysts showed better performance. The good performance can be attributed to the good dispersion of V species, presence of V 4+ species and the pore structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 40 publications
2
25
0
2
Order By: Relevance
“…Nevertheless, there have been only few reports on the application of SBA-15-supported vanadium oxide as catalyst for selective oxidation reactions. [21,22,[40][41][42][43][44][45] A different approach to powder vanadium oxide model catalysts is based on the controlled synthesis of molecular compounds, for example, vanadium calixarene complexes. [46,47] Figure 1 shows typical SEM and TEM images of a sample prepared by controlled synthesis with a vanadium loading of 3.3 wt % (V/SBA-15), which corresponds to a vanadium atom density of 0.8 V nm…”
Section: Controlled Synthesis Based On Spectro-a C H T U N G T R E N mentioning
confidence: 99%
“…Nevertheless, there have been only few reports on the application of SBA-15-supported vanadium oxide as catalyst for selective oxidation reactions. [21,22,[40][41][42][43][44][45] A different approach to powder vanadium oxide model catalysts is based on the controlled synthesis of molecular compounds, for example, vanadium calixarene complexes. [46,47] Figure 1 shows typical SEM and TEM images of a sample prepared by controlled synthesis with a vanadium loading of 3.3 wt % (V/SBA-15), which corresponds to a vanadium atom density of 0.8 V nm…”
Section: Controlled Synthesis Based On Spectro-a C H T U N G T R E N mentioning
confidence: 99%
“…Figure 8 shows that the relative peak intensities of the 29 . However, the intensity ratios of these peaks corresponded well to the model structure (8). Unidentified minor resonances in Fig.…”
Section: Gel Formation Processmentioning
confidence: 67%
“…Since the molar ratio of TEOS/ V(OR) was kept at 16.7 (for a sample containing 1.0 mmol of V), the terminal _ OH groups of PEG25 were less likely to react with two V(OR). Vanadium was incorporated in the process of polycondensation of TEOS, as in (7), and two-and three-dimensional crosslinking then formed a simple model structure as in (8) by repeated reactions, as shown in Scheme 1. Silicon atoms at the four corners of (8) were linked with two PEG25.…”
Section: Gel Formation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that the V 4+ ion in association with oxygen vacancies acts as an active species [13,15]. A remarkable good performance in butane ODH has been attributed to the good dispersion of V species, the presence of V 4+ species and the pore structure [16]. It is well known that tetrahedral V is the active species but its environment remains controversial.…”
Section: Introductionmentioning
confidence: 99%